2013
DOI: 10.1055/s-0032-1333131
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Nosocomial Infections in Neonatal Intensive Care Units

Abstract: Sepsis-related morbidity and mortality is an increasing concern in all neonatal intensive care units (NICUs), and the reported incidences are dramatically high regardless of the improvements in the quality of neonatal assistance. 1 Neonatal sepsis includes bloodstream, urine, cerebrospinal, peritoneal, and lung infections, as well as infections starting from burns and wounds or from any other usually sterile site. It is associated with cytokine-and biomediatorinduced disorders of respiratory, hemodynamic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In humans, LF is known to be able to prevent the onset of sepsis in infants [46–48]. LF has a high homology among species [49] thus, heterologous molecules of LF are used as a therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, LF is known to be able to prevent the onset of sepsis in infants [46–48]. LF has a high homology among species [49] thus, heterologous molecules of LF are used as a therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…is associated with prolonged antibiotic treatments, delayed enteral feeding, or nursing in incubators and translates into proliferation of pathogenic microflora and abnormal gut colonization. Seemingly, enhancement of the enteric microbiota composition with supplementation of probiotics seems to be a good strategy to prevent sepsis and could also be applied to prevent neonatal VAP [72]. Nevertheless, a recent meta-analysis of 7 randomized controlled trials conducted in adult populations concluded that probiotics showed no beneficial effect in patients who are mechanically ventilated, did not significantly decrease the incidence of VAP, and should not be recommended for routine clinical application [73].…”
Section: Preventionmentioning
confidence: 99%
“…Furthermore, early life colonization deficiencies have been associated with alterations in host metabolism and immune function (18, 19). In the neonatal intensive care unit (NICU), however, the promotion of potentially beneficial host-microbe interactions must be carefully balanced against the control of pathogen spread among a highly vulnerable patient population (20, 21). This is distinctively challenging with regard to the prevention and treatment of NEC, a disease in which the interrelated roles of antibiotic exposure, enteral feedings, and changes in the intestinal microbiota are imprecisely defined (10, 11).…”
Section: Introductionmentioning
confidence: 99%